Evaluation framework of community-based livestock breeding programs - Lamuno, Doreen; Sölkner, Johann; Mészáros, Gabor; Nakimbugwe, Helen; Mulindwa, Henry; Nandolo, Wilson; Gondwe, Timothy; van Tassel, Curt; Mueller, Joaquin Pablo; Wursinger, Maria; Gutierrez, Gustavo (2018)
The objective of this paper is to present an evaluation framework to provide guidance for an assessment of the performance, outputs and associated impacts of community-based livestock breeding programs (CBBPs), responding to the need of formalizing the evaluation procedures as it was stressed by FAO. The purpose of such evaluation is to monitor and evaluate on-going activities in CBBPs, to identify challenges and mistakes in the execution of the program, so that appropriate actions can be taken. This evaluation also serves as a guide for funding bodies to measure socio-economic impact on the livelihoods of livestock farmers in order to decide if the program’s goals have been met. The evaluation framework is divided into three domains: evaluation of CBBP implementation based on organizational and technical criteria; monitoring of implementation outputs to evaluate genetic improvement at herd/flock level and the consequential changes at the household level and the community at large; and evaluation of impacts to assess improvement in livelihoods of livestock farmers and eventual effects on the environment. For each evaluation criteria, several indicators are provided.